(untitled) (Research, Society and Development, 2021)
Objective: identify national and international scientific evidence on the potential, demands and weaknesses in the profile of nursing care for children who are victims of burns. Method: Integrative literature review, carried out in four databases, with the inclusion criteria: full articles, free access, available online, languages in English, Spanish and Portuguese. The final sample consisted of 10 studies. Results: From the reading and comparison between the results of the studies, four categories emerged, organized into: strengths, demands and weaknesses in caring for children who were victims of burns. Conclusion: In the selected studies, we identified strengths, weaknesses and demands. Although potentials, such as an articulated network, autonomy in care, welcoming and empathy; there are weaknesses, such as lack of effective communication strategies and inadequate recording of information, which challenge the implementation of comprehensive care.